1988
DOI: 10.1523/jneurosci.08-06-01991.1988
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition in kainate-lesioned hyperexcitable hippocampi: physiologic, autoradiographic, and immunocytochemical observations

Abstract: Following kainate lesions of hippocampal subfield CA3, the remaining CA 1 pyramidal cells become hyperexcitable. This lesion is of interest because, morphologically, it resembles the damage often seen in cases of temporal lobe epilepsy; it may provide insight into the consequences of such cell loss in humans. The hyperexcitability in CA 1 is associated with a loss of both early and late IPSPs. At long postlesion latencies (2–4 months) inhibition shows partial recovery and the hyperexcitability subsides. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(75 citation statements)
references
References 29 publications
5
70
0
Order By: Relevance
“…Likewise, the graded bursts recorded from the lesioned slices ( Fig. 2; Franck et al, 1988) were significantly different from the structured bursts associated with acute loss of postsynaptic inhibition (Dingledine and Gjerstad, 1980;Wheal et al, 1984), suggesting that more features are present than the loss of the inhibitory drive alone. Thus, the present findings are not compatible with the loss of inhibitory drive as the sole mechanism leading to hyperexcitability, and changes in the predominant receptor mechanisms underlying the EPSP (non-NMDA and NMDA) appear to have a significant role in the hyperexcitability.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Likewise, the graded bursts recorded from the lesioned slices ( Fig. 2; Franck et al, 1988) were significantly different from the structured bursts associated with acute loss of postsynaptic inhibition (Dingledine and Gjerstad, 1980;Wheal et al, 1984), suggesting that more features are present than the loss of the inhibitory drive alone. Thus, the present findings are not compatible with the loss of inhibitory drive as the sole mechanism leading to hyperexcitability, and changes in the predominant receptor mechanisms underlying the EPSP (non-NMDA and NMDA) appear to have a significant role in the hyperexcitability.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, the present findings may be a phase in response to the denervation, and some degree of recovery may occur over several weeks (Cavalheiro et al, 1982), as suggested by anatomical studies of denervation and plasticity (Nadler et al, 1980a,b, Cotman andNeito-Sampedro, 1984;Phelps et al, 199 1). Though paired-pulse facilitation (as a result of failure of early pairedpulse inhibition) continued in vivo for weeks after a KA lesion (Cornish and Wheal, 1989) other groups studying the KA model have suggested an eventual partial recovery from the hyperexcitability associated with the KA lesion (Franck et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations